ANALISIS PENGARUH DANA DESA TERHADAP PEMULIHAN EKONOMI DAERAH (Studi Kasus 30 Kab/ Kota Provinsi Jawa Timur TA 2017-2021) - Haya, Aulia Aqila; Agus Suman (Journal of Development Economic and Social Studies, 2023)
This study projects regional economic recovery through economic growth and the number of poor people to evaluate the role of village funds. Corona Virus Disease (COVID19) is a national emergency, according to KEPPRES No. 12 of 2020. This research focuses on the slowdown in economic growth and an increase in the number of poor people in 30 regencies/cities in East Java Province. Budget reallocation and refocusing are used to maintain regional financial stability. According to regulations from the Ministry of Villages of PDTT, the implementation of economic recovery depends on being supported by a reallocation of the village fund budget that should be allocated for village empowerment and development. Panel data regression analysis is an appropriate methodology for this study because it projects a specific timeframe. According to research, village funds in 30 regencies and cities in East Java Province for 2017 to 2021 fiscal year significantly affect economic growth and the number of poor people.